Real fantasies : Edward Steichen's advertising photography - Johnston, Patricia A., 1954- (Berkeley, Calif. : University of California Press, 1997)
"During the 1920s and 1930s, Edward Steichen was the most successful photographer in the advertising industry. Although much has been said about his fine-art photography, his commercial work - which appeared regularly in Vanity Fair, Vogue, Ladies' Home Journal, and other popular magazines - has not received the attention it deserves."--BOOK JACKET. "In this book, Patricia Johnston uses Steichen's work as a case study of advertising photography as it developed in the consumer culture between the wars. She traces the evolution of Steichen's work from an early naturalistic style through increasingly calculated attempts to construct consumer fantasies. Steichen's work convinced advertising agents that photography was a far more effective medium for engaging and persuading consumers than the more traditional drawn illustrations."--BOOK JACKET. "Johnston presents an intriguing view of advertising agencies from the inside. Using agency archives, she reconstructs the teamwork of clients, art directors, account executives, copywriters, and photographers. And she goes on to assess how these widely distributed images work in American culture - how they interact with their audience to express, reflect, shape, and challenge social values."--Jacket
1. Patronage and Style in Steichen's Early Work -- 2. The Age of Corporate Patronage: Advertising Accelerates the Demand for Photography -- 3. From "Reality" to "Fantasy" in Early Photographic Advertising -- 4. Subtle Manipulations: The Persuasion of Realism -- 5. The Modern Look in Advertising Photography and Product Design -- 6. The Collaborative Image -- 7. Testaments to Class Mobility -- 8. Viewing Fine and Applied Art: The Female Spectator and Advertisements -- 9. Melodrama in Black and White and Color -- 10. Ethnographic Advertising
BIBINDX
Keywords: Steichen, Edward, -- 1879-1973; Advertising photography -- United States -- History